2022
DOI: 10.5588/pha.21.0071
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic resistance in patients with urinary tract infections in Pakistan

Abstract: BACKGROUND: The level of antibiotic resistance of pathogens causing uncomplicated urinary tract infections (UTIs) is increasing. The 2017–2018 GLASS (Global Antimicrobial Resistance and Use Surveillance System) report indicated >70% resistance to ceftriaxone and ciprofloxacin in Escherichia coli in Pakistan.METHODS: A prospective study was conducted in the Médecins Sans Frontières (MSF) supported Timurgara District Hospital, Timurgara, Pakistan, from September 2017 to December 2018. Women aged 18–65 years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 9 publications
1
12
0
6
Order By: Relevance
“…Previous studies have indicated the non-judicious use of quinolones in hospitalized individuals, where a significant proportion of these antimicrobials are administered prophylactically to prevent hospital-acquired infections. Second, ciprofloxacin is widely used for the treatment of urinary tract infections, the most common complaint in adults requiring antibiotic treatment [ 40 ]. Additionally, quinolones are also prescribed extensively for the treatment of upper and lower respiratory tract infections, in most cases without sensitivity testing [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated the non-judicious use of quinolones in hospitalized individuals, where a significant proportion of these antimicrobials are administered prophylactically to prevent hospital-acquired infections. Second, ciprofloxacin is widely used for the treatment of urinary tract infections, the most common complaint in adults requiring antibiotic treatment [ 40 ]. Additionally, quinolones are also prescribed extensively for the treatment of upper and lower respiratory tract infections, in most cases without sensitivity testing [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is, therefore, imperative that the principles of an ASP are applied to both the inpatient and outpatient settings, to truly have a significant impact on reducing the threat of antimicrobial resistance [ 42 ]. Furthermore, an ASP in the outpatient setting must be designed in a way that can be adapted by a variety of institutions with ease and efficiency, regardless of the facilities’ finances, endorsements, and resources available [ 3 ].…”
Section: Artificial Intelligence Vs Antibiotic Stewardship Programmentioning
confidence: 99%
“…However, the widespread use of antibiotics in clinical practice has resulted in drug resistance, in addition to increasing the threat of super-resistant bacteria emergence [ 2 ]. Antimicrobial resistance (AMR) is anticipated to cause around 10 million deaths per year by 2050, and the economic impact of AMR is expected to approach USD 100 billion during the same period [ 3 ]. It is imperative that required efforts to implement new regulations and revive research efforts to manage the AMR epidemic are carried out to address this crisis [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…WHO GLASS (Global Antimicrobial Resistance and Use Surveillance System) report of 2017-2018 points out resistance of >70% towards ceftriaxone and ciprofloxacin in E. coli isolated from urinary tract infection in Pakistan 4 . In Pakistan resistance to Fosfomycin is low as there was only one reported case in the Bullens et al study in an isolate of E. coli 5 . Resistance to Fosfomycin from other parts of the world is reported as 8.3% in Italy, 4.6% in Spain, 2.9% in the UK (United Kingdom), and 1.9% from Belgium and Russia 6 .…”
Section: Introductionmentioning
confidence: 95%